Placentation in the rock cavy, Kerodon rupestris (Wied) - Oliveira, M. F.; Carter, A. M.; Bonatelli, M.; Ambrosio, C. E.; Miglino, M. A. (W B Saunders Co Ltd, 2006)
Rock cavies are rodents found in the semi-arid caatinga of Brazil. We studied the structure of the rock cavy placenta by light and transmission electron microscopy. The exchange area of the labyrinth was organized in lobes separated by interlobular areas. The interhaemal barrier was syncytial haemomonochorial. The syncytiotrophoblast had recesses in the basal membrane and some invaginations of the apical membrane, but transtrophoblastic channels could not be found. The interlobular regions comprised syncytiotrophoblast, enclosing maternal venous blood channels, and cytotrophoblast. There was a prominent subplacenta composed of cytotrophoblast and syncytiotrophoblast. Microvilli projected into spaces between the cytotrophoblasts and into lacunae within the syncytiotrophoblast. The yolk sac epithelium exhibited coated pits, endocytotic vesicles and larger vacuoles, consistent with a role in protein uptake from the uterine lumen. Tight junctions between these cells provided a barrier to diffusion by the intercellular route. The reproductive biology of the rock cavy differs from other members of the family, including the guinea pig, but the architecture of the placenta remains remarkably constant. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: hystricomorph; hystricognath; rock cavy; placenta; subplacenta; yolk sac; fetal membranes; ultrastructure